Keefektifan Keefektifan Model Pembelajaran Contextual Teaching Learning (CTL) dan Problem Based Learning (PBL) pada Mata Pelajaran IPA Kelas VI terhadap Kreativitas dan Hasil Belajar - Achmad Samsudin; Tri Joko Raharjo; Widiasih (Postgraduate, University of Mataram, 2023)
The aim of the research is to analyze the mastery of creativity and student learning outcomes through Contextual Teaching Learning (CTL), Problem Based Learning (PBL) and expository learning models, as well as knowing the differences in increasing creativity and learning outcomes after learning in the three learning models. The research design uses true–experimental research. The research sample is 21 class VI students at SDN 1 Tamanrejo and 22 students at SDN 2 Tamanrejo the experimental group, and 19 students at SDN Trimulyo as control group. Data analysis used one way anova and paired sample t-test. The results show that achievement of classical completeness in science learning outcomes with the CTL learning model = 85.7%; PBL = 63.5%; and expository = 15.8%. Increased learning creativity in the CTL learning model, learning creativity increased by 45.25%; PBL 34.52%; and expository 25.80%. The increase in student science learning outcomes in classes with the CTL learning model increased by 89.18%; PBL 73.17%; and expository 57.10%. The conclusion of the research shows that CTL model classes produce better learning creativity and complete science learning outcomes compared to classes that apply the PBL model and higher than those that apply the expository model.